The impact of enriched environments on cerebral oxidative balance in rodents: a systematic review of environmental variability effects - Ramos, Tiago Lacerda; de Sousa Fernandes, Matheus Santos; da Silva Fidélis, Débora Eduarda; Jurema Santos, Gabriela Carvalho; Albuquerque, Renata B.; Ferreira, Diorginis José Soares; de Souza, Raphael Fabrício; Badicu, Georgian; Yagin, Fatma Hilal; Yagin, Burak; Alwhaibi, Reem M.; Souto, Fabrício Oliveira; et al. (Frontiers in Neuroscience, 2024)
The present review aimed to systematically summarize the impacts of Environmental Enrichment (EE) on cerebral oxidative balance in rodents exposed to normal and unfavorable environmental conditions. In this systematic review, four databases were used: PubMed [830 articles], Scopus [126 articles], Embase [127 articles], and Science Direct [794 articles]. Eligibility criteria were applied based on the PICOS (Population / Intervention/ Control/ Outcomes/ Study) strategy to reduce the risk of bias. The searches were carried out by two independent researchers; in case of disagreement, a third participant was requested. After selection and inclusion of articles, data related to sample characteristics and the EE protocol (time of exposure to EE; number of animals; size of the environment) were extracted, as well as data related to brain tissues and biomarkers of oxidative balance, including carbonyls; malondialdehyde; nitrotyrosine; oxygen-reactive species; glutathione (reduced/oxidized). 1877 articles were found in the four databases, of which 16 studies were included in this systematic review. The results showed that different EE protocols were able to produce a global increase in antioxidant capacity, both enzymatic and non-enzymatic, which are the main factors for the neuroprotective effects in the Central Nervous System subjected to unfavorable conditions. Furthermore, it was possible to notice a slowdown in neural dysfunction associated with oxidative damage, especially in the prefrontal structure in mice. In conclusion, environmental enrichment protocols were determined to be valid tools for improving oxidative balance in the Central Nervous System. The global decrease in oxidative stress biomarkers indicates refinement in Reactive Oxygen Species detoxification, triggering an improvement in the antioxidant network.